Improving Students' Biology Learning Outcomes Through the Implementation of a Guided Inquiry Model - Modi, Moh.; Ansori, Dias; Shofiyuddin, Shofiyuddin; Amanah, Isbatul; Kaharuddin, Moh. (Lombok Institute, 2024)
This study aims to improve the biology learning outcomes of 10th-grade students at Madrasah Aliyah Miftahul Ulum Bettet Pamekasan, Madura, by implementing the guided inquiry model. This classroom action research was conducted during the odd semester of the 2023-2024 academic year, involving 40 students as subjects. Data collection was carried out using pre-tests and post-tests for each Cycle to measure learning outcomes. The results indicated that applying the guided inquiry model could enhance students' biology learning outcomes. In the first Cycle, the average learning score was 78, with a completion rate of 65%. Following adjustments and improvements, the second Cycle saw an increase in the average learning score to 85, with a completion rate of 90%. These findings suggest that the guided inquiry model can be an effective alternative in biology teaching to improve students' learning outcomes at Madrasah Aliyah. The implications of this study provide a basis for developing more interactive and participatory teaching methods.